The regulation of ukuthwala in South Africa: lessons from Malawi - Saukila, Tonthozo (Department of Public Law, 2023)
South Africa is a pluralistic society whose supreme constitution protects the right to culture and other fundamental human rights, such as the right to equality and human dignity. South Africa is also party to a number of international and regional human rights instruments which aim to protect women and children from discrimination and harmful practices. It is important to consider these instruments as they create the normative standards to which South Africa is bound. Today, the continued practice of certain cultural practices, which are seen as inherently cultural, risk the violation of the Constitution and international and regional instruments. This thesis examines the tension between the right to culture and, inter alia, the right to dignity and equality, through the practice of ukuthwala. Ukuthwala, also known as bridal abduction, is mainly prevalent in the Eastern Cape and Kwazulu Natal provinces of South Africa, though it is also practiced in other provinces of the country. It aims to address the question: how can south Africa regulate ukuthwala? In coming to an answer, this thesis examines how Malawi has regulated the harmful cultural practice (HCP) of child marriage. Like South Africa, Malawi is a pluralistic society with a supreme constitution which protects, inter alia, the right to participate in the cultural life and the right to human dignity and personal freedoms. In line with its international and regional human rights obligations, Malawi has promulgated legislation to formally regulate HCPs. However, such “top-down” interventions are not always the best approach in African societies, as they are often theoretically beneficial to those they aim to help, but practically do not help. As such, there is a need for a “bottom-up” approach, one that involves the community, in creating solutions that regulate the HCPs affecting them. In this regard, various communities in Malawian districts have employed community “by-laws”, which are community made rules and sanctions that are not legally binding, to combat HCPs. The thesis argues that such by-laws, though non-binding, are effective because they provide a community owned and oriented solution, which inspires adherence. As such, they have contributed to reducing the prevalence of child marriage in the country. It argues that such a “bottom-up” approach is best suited to address HCPs in rural communities, as it is a home-grown solution. This thesis proposes an adapted form of community “by-laws” be employed in the context of ukuthwala, as it counters the alienation sometimes caused by the “top-down” approach. In including the community in creating a solution, they are involved in creating solutions which address the problems specific to them, and they are given ownership of the solution.